Análise de gênero: investigação da organização retórica de notícias de popularização da ciência na revista Ciência Hoje online - Lovato, Cristina dos Santos (2010)
This research aims to identify and to interpret the rhetorical organization of science popularization news, published in the journal Ciência Hoje Online, providing a schematic description of the rhetorical organization of these texts and an interpretation of this organization by surveying aspects related to the context of production of the news. The theoretical background used for the development of the research is the Genre Analysis formulated by Swales (1990, 2004). The corpus is comprised by 30 exemplars of the genre covering themes related to topics of health and environment. The analysis was divided into two steps: textual analysis and contextual analysis. The procedures for textual analysis have an interpretative basis as a way to describe linguistic elements concerning each rhetorical move (BHATIA, 1993, p. 22). The point of departure to carry out this step was the representation of the rhetorical organization of science popularization news genre elaborated by Motta-Roth and Lovato (2009, p. 246). The procedures for contextual analysis are also interpretative and they are based on documents from the magazine s website as well as from interviews with genre s participants. The results indicate a rhetorical organization of the news analyzed in six rhetorical moves, high incidence of code glosses and direct and indirect discourses as recursive elements. The exclusive presence of the voice of the scientist responsible for the research popularized to explain and debate the reported study shows that, in the news of Ciência Hoje Online, the dominant view of science prevails (HILGARTNER, 1990). This prevalence gives to these texts a monologue character (MOTTA-ROTH; LOVATO, 2009), since just the researcher evaluates the study reported. This way, the hegemonic power of science is maintained in the discourse of popularization.